(untitled) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY To assess the health-seeking behaviour, the patient delay (onset of symptoms to first consultation) and the health system delay (first consultation to start of tuberculosis treatment) among patients with pulmonary tuberculosis (TB) diagnosed in Switzerland, and to assess the predictors of the various types of delay. METHODS A survey among pulmonary TB patients was carried out in six cantons, covering 42% of all pulmonary adult TB cases notified in Switzerland. Data were collected by collaborators of the cantonal lung associations in charge of the follow-up of TB patients to investigate treatment seeking behaviour and to establish various delays and its predictors. Predictors of percentiles of delay (median and 75th percentile) were assessed using quantile regression. RESULTS Among 252 eligible patients, 162 patients could be interviewed. Of these, 20.4% were born in Switzerland. Cough as a symptom was mentioned by 76% of the interviewed patients. Almost half of the 162 patients (46%) consulted first a general practitioner in an ambulatory care setting and 26% approached a hospital first. The median delay between symptom onset and first healthcare contact (patient delay) was 5.2 weeks, which is slightly longer than findings in other low prevalence countries. The interquartile range was 1.6 to 14.2 weeks. The median delay between first consultation in Switzerland and the start of TB treatment (health system delay) was 2 weeks. The interquartile range was 0.6 to 7.1 weeks. ​ There were no clear predictors of patient delay. The main predictors of a longer median health system delay were the presence of fever (1.6 weeks, 95% confidence interval [CI] 0.5 to 2.6 weeks), having visited first a general practitioner or a paediatrician (1 week, 95% CI 0.1 to 1.9 weeks) and having seen three or four doctors before beginning TB treatment (2.9 weeks, 95% CI 0.7 to 5.1 weeks). A clear predictor of a shorter median health system delay was having undergone an X-ray at the first consultation (−2.9 weeks, 95% CI −4.8 to −0.9 weeks). Marginally significant for shorter delay was male sex (−2.6 weeks, 95% CI −5.4 to 0.1 weeks). CONCLUSIONS No predictor of patient delay was found among the variables collected. For one fourth of the patients, the health system delay was longer than 7 weeks. General practitioners are commonly approached first, and they have to consider TB, also for patients not considered at high-risk for TB.